Reversibility Time in Testicular Damage on Male Wistar Rat after Treatment of Averrhoa blimbi L. Fruits Extract as Antifertility - Alipin, Kartiawati; Rochman, Indra A.; Malini, Desak M.; Madihah, Madihah (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Belimbing wuluh (Averrhoa blimbi) fruit is commonly used traditionally as antifertility. The bioactive compounds of A. blimbi have been known could inhibit spermatogenesis and development of testes, as well as decrease the quality and quantity of spermatozoa, thus, caused seminiferous tubular atro- phy. This study aimed to determine the reversibility time in testicular damage after the treatment of A. blimbi fruit extract on male Wistar rat. The method employed a completely randomized design (CRD) consists of nine treatments with three replications each. The treatment of the extract at a dose 1140 mg/ kg BW and control group was given the solvent. After 14 days of treatment, the reversibility time was examined in testis histological section by interval of seven days each until 49 days. The results showed that the treatment of A. blimbi fruit extract caused disruptions in seminiferous tubules, i.e. decreased the number of spermatogonium and spermatid, as well as the diameter of lumen and seminiferous tu- bules. The reversibility time was observing at 21 days after the end extract treatments, by increasing the number of of spermatogonium and spermatid, as well as the diameter of lumen and seminiferous tubules that signi cantly different with infertile rat (p<0.05). In conclusion, the reversibility time was 21 days after the treatment of A. blimbi fruit extract as antifertility. Key words: Averrhoa blimbi, rats, reversible time, tubulus seminiferous